1-(6-Fluoro-1,3-benzothiazol-2-yl)-3-phenyl-1H-pyrazole-4-carbaldehyde - Fun, Hoong-Kun (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C(17)H(10)FN(3)OS, consists of two crystallographically independent molecules. In one molecule, the pyrazole ring makes dihedral angles of 6.51 (7) and 34.02 (9)°, respectively, with the terminal 1,3-benzothiazole ring system and the phenyl ring, while in the other molecule these values are 6.41 (8) and 23.06 (9)°. In the crystal, the molecules are linked by weak π–π [centroid–centroid distance = 3.7069 (10) Å] and C—H⋯π interactions.